Interaction of Coenzyme Q10 with Liposomes and its Impact on Suppression of Selenite - Induced Experimental Cataract - Medhat Wahba Shafaa; Amany Hasan Elshazly; Amira Zaki Dakrory; Maha Reda Elsyed (Tabriz University of Medical Sciences, 2018)
Purpose: To stress the influence of Coenzyme Q10 (CoQ10) on the structural properties of liposomes as model membranes and to investigate the possible role of CoQ10 or CoQ10 doped in liposomes when topically instilled as eye drops, in preventing cataract. Methods: The molecular interaction between liposomes and Coenzyme Q10 was examined using differential scanning calorimetry (DSC) and Fourier transform infrared spectroscopy (FTIR). Rat pups were randomly divided into six groups comprising 15 pups. Group (1), control group. Group (2), untreated model of cataract, received a single subcutaneous injection of sodium selenite. Instillation of pure CoQ10 (Group 3), CoQ10 encapsulated into neutral (Group 4), positive (Group 5) and negative (Group 6) Dipalmitoyl phosphatidylcholine (DPPC) liposomes on the opacification of lenses in rat pups after sodium selenite injection was topically received. Results: The incorporated CoQ10 is probably associated with lipid bilayers where it interacts to a large extent and perturbs them. This results in strong broadening and shift to lower temperature (94°C) of the major characteristic endothermic peak of pure DPPC at 105°C. FTIR showed that the incorporation of CoQ10 into DPPC induces a conformational change in the polar region of DPPC. Ophthalmological and Biochemical studies revealed that CoQ10 alone followed by negatively charged liposomes doped with CoQ10 are more effective in reducing the progress of cataract as well as improving the lens soluble proteins levels and total antioxidant capacity. Conclusion: The interactions of CoQ10 with membrane systems may contribute to a better understanding of CoQ10 physiological properties and the development of therapeutically advanced systems.